The Linkages Effect of Service Quality, Customer Satisfaction and Customer Loyalty of Automobile Financing within the Malaysia Islamic Banking Industry - W Muhammad Zainuddin Wan Abdullah; Wan Nur Rahini Aznie Zainuddin; Muhammad Ridhwan Ab. Aziz (Universiti Sains Islam Malaysia, 2024)
Nowadays, Islamic banks are facing tough competition among themselves and conventional banks that offer services and banking products based on Islamic principles. Such competition leads to issue involving customer satisfaction regarding the Islamic financing products and the efficiency of the services offered. Thus, the aims of this paper is to investigate the linkage effect of service quality (efficiency) on customer satisfaction and customer loyalty of Islamic automobile financing in Malaysia. Survey data was collected from 584 walk-in customers of selected bank outlets in the state of Selangor, Wilayah Persekutuan Kuala Lumpur and Putrajaya. The data was then analysed using Pearson Correlation and Multiple Regression technique. Results show that customer satisfaction and customer loyalty were positively affected by quality of service offered by Islamic Banks. Hence, based on the results, Islamic bank should have an effective computerised system, good legal advisory, Islamic compliance, well-trained staff, secure transaction, sufficient bank branches, and as well as sufficient facility and information in order to uplift and improve efficiency of the bank.